Characterization of Trypanosoma brucei MICOS subunit Mic20. - Deisenhammer, Sebastian (Jihočeská univerzita, 2021)
This study focuses on the trypanosome MICOS complex related membrane protein Tb927.10.11900 (TbMic20) in Trypanosoma brucei. This research aimed to express TbMic20 in E. coli cells under soluble conditions and further determine its standard redox potential.
Characterization of Trypanosoma brucei MICOS subunit Mic20.
Keywords: trypanosoma brucei; recombinant protein; mitochondria; redox potential; trypanosoma brucei; recombinant protein; mitochondria; redox potential